Long-Term Spatial and Temporal Variation of Near Surface Air Temperature in Southwest China During 1969–2018 - Zhou, Jia; Lu, Tao (Frontiers in Earth Science, 2021)
Near surface air temperature (NSAT) is one of the most important climatic parameters and its variability plays a vital role in natural processes associated with climate. Based on an improved ANUSPLIN (short for Australian National University Spline) model which considers more terrain-related factors, this study analyzed the trends, anomalies, change points and variations of NSAT in Southwest China from 1969 to 2018. The results revealed that the improved approach performed the best in terms of Mean Absolute Error (MAE), Root Mean Square Error (RMSE) and R-squared (R2) comparing to the conventional ANUSPLIN and co-kriging methods. It has great potential for future meteorological and climatological research, especially in mountainous regions with diverse topography. In addition, Southwest China experienced an overall warming trend of 0.21 ℃/decade for annual mean NSAT in the period 1969-2018. The warming rate was much higher than mainland China and global averages, and statistically significant warming began in the late 1990s. Moreover, consistent warming and significant elevation-dependent warming (EDW) were observed in most parts of Southwest China, and the hiatus or slowdown phenomenon after the 1997/1998 El Niño event was not observed as expected. Furthermore, the remarkable increase in winter and minimum NSATs contributed more to the whole warming than summer and maximum NSATs. These findings imply that Southwest China responds to global warming more sensitively than generally recognized, and climate change in mountainous regions like Southwest China should be of particular concern.